Dispersal of coral larvae within inshore reefs of Kuantan coastal waters - Muhammad Faiz bin Mohd Hanapiah (Kulliyyah of Science, International Islamic University Malaysia, 2020)
Inshore reefs areas play several important ecosystem functions in marine environment especially in coastal area. Eight reef sites were surveyed using coral video transect (CVT) technique between April 2017 and April 2019 in Balok reef and Raja Muda reef to estimate coral reef benthic components. The timing of coral spawning of two Acropora species; Acropora cytherea and Acropora clathrata was estimated through dissection and histological analyses of coral fragments that were collected during predicted spawning months (March until May 2018) from Balok reef, Kuantan. In addition, physicochemical parameters (sea temperature, salinity and pH) were measured from March until September 2018 by multiprobe parameter. Satellite image was extracted between 2014 and 2018 from Aqua MODIS to observe seasonal pattern of sea surface temperature. Hydrodynamic model of Kuantan coastal water was simulated using MIKE 21 Flow Model FM and validated using 4 series of in situ current speed and direction data measured by Acoustic Doppler Current Profiler (ADCP) between August 2017 and April 2018. Dispersal pattern of coral larvae among three known inshore reefs (Pulau Ular, Balok Reef and Raja Muda reef) in Kuantan coastal waters was elucidated by simulating virtual larvae trajectories during spawning event in 2018. Dispersal pathways were modelled and constructed by incorporating biological traits (timing of spawning and pelagic larvae duration) using Lagrangian particle tracking module integrated with 2-dimensional, hydrodynamic, flexible network model (MIKE 21 FM). Dispersal Potential Index (DPi) was developed based on four important factors described throughout this thesis (adult coral cover, pelagic larvae duration, current speed and depth variation) to estimate dispersal potential capacity of coral larvae. Data analysis on coral reef benthic components indicated that Kuantan coastal waters has 'fair' coral cover with average percentage of 40.2 % ± 10.65 in which Angly 3 (ST3) recorded the highest live coral cover coverage with 50.3%. Abiotic components (sand and rock) were the second-most abundant and the coverage of dead coral was relatively low at all stations. Coral spawning observation of two Acropora species; Acropora cytherea and Acropora clathrata indicate spawning of these broadcast spawners occurred following full moon in April 2019. This finding confirmed histological examinations in the previous year (2018) that spawning for this genus might occur in April 2019. The gamete maturity coincided with the peak sea surface temperature within Kuantan coastal waters from April until May 2018. Optimal pelagic larvae duration for these species were estimated to be between 6 – 8 days after spawning. Hydrodynamic model indicated the prevalence of tidal forcing in influencing current flow in Kuantan coastal region rather than seasonal changes by monsoonal winds. Virtual larvae simulation indicated Pulau Ular has high larvae retention (76 %) in which most of larvae originated from natal reef. Balok reef was dominant source of larvae for Raja Muda reef. Results also indicated that patches reefs near Raja Muda was ideal sink site for coral larvae and should be prioritized for future ecosystem management action. It is believed that findings from this research could give reliable scientific on dispersal of coral larvae within inshore reefs of Kuantan coastal waters.